A community‐based study on determinants of circulating markers of cellular immune activation and kynurenines: the Hordaland Health Study. (6th June 2013) - Theofylaktopoulou, D.; Midttun, Ø.; Ulvik, A.; Ueland, P. M.; Tell, G. S.; Vollset, S. E.; Nygård, O.; Eussen, S. J. P. M.
Summary Circulating neopterin and kynurenine/tryptophan ratio (KTR) increase during inflammation and serve as markers of cellular immune activation, but data are sparse on other determinants of these markers and metabolites of the kynurenine pathway. We measured neopterin, tryptophan, kynurenine, anthranilic acid, kynurenic acid, 3‐hydroxykynurenine, 3‐hydroxyanthranilic acid and xanthurenic acid in plasma in two age groups, 45–46 years (n = 3723) and 70–72 years (n = 3329). Differences across categories of the potential determinants, including age, gender, renal function, body mass index (BMI), smoking and physical activity, were tested by Mann–Whitney U‐test and multiple linear regression including age group, gender, renal function and lifestyle factors. In this multivariate model, neopterin, KTR and most kynurenines were 20–30% higher in the older group, whereas tryptophan was 7% lower. Men had 6–19% higher concentrations of tryptophan and most kynurenines than women of the same age. Compared to the fourth age‐specific estimated glomerular filtration rate (eGFR) quartile, the first quartile was associated with higher concentrations of neopterin (25%) and KTR (24%) and 18–36% higher concentrations of kynurenines, except 3‐hydroxyanthranilic acid. Additionally, KTR, tryptophan and all kynurenines, except anthranilic acid, were 2–8% higher in overweight and 3–17% higher in obese, than in normal‐weight individuals. Heavy smokers had 4–14% lower levels of tryptophan and most kynurenines than non‐smokers. Age and renal function were the strongest determinants of plasma neopterin, KTR and most kynurenines. These findings are relevant for the design and interpretation of studies investigating the role of plasma neopterin, KTR and kynurenines in chronic diseases.